A prototype knowledge-based system for material selection of ceramic matrix composites of automotive engine components - Salit, Mohd Sapuan; Devanesan Jacob, M. Suresh; Mustapha, Faizal; Ismail, Napsiah (Elsevier, 2002)
A prototype knowledge based system (KBS) for material selection of ceramic matrix composites (CMC) for engine components such as piston, connecting rod and piston ring is proposed in this paper. The main aim of this research work is to select the most suitable material for the automotive engine components. The selection criteria are based upon the pre-defined constraint value. The constraint values are mechanical, physical properties and manufacturing techniques. The constraint values are the safety values for the product design. The constraint values are selected from the product design specification. The product design specification values are selected from the past design calculation and some values are calculated by the help of past design data. The knowledge-based system consists of several modules such as knowledge acquisition module, inference module and user interface module. The domains of the knowledge-based system are defined as objects and linked together by hierarchical graph. The system is capable of selecting the most suitable materials and ranks the materials with respect to their properties. The design engineers can choose the required materials related to the materials property.